Notating folk dances a guideline on the design of performing arts complex in the Philippines - Fadriquela, Peben Jay F. (2018)
The study aimed to produce a design guideline for a performing arts complex in the Philippines through notating folk dances using Labanotation. Folk dances in the Philippines are misrepresented due to modernization and adaptation of other cultures. Through notation, these dances will be preserved and will be used by the future performers and dance director and at the same time guide the designers of theater performing areas in allocating enough space for the performance. The chosen festival folk dances to be notated will not only be preserved but the future performers will represent the original actions. Books and videos were used as a reference to identify and verify the actions of the different dances. There were six festival folk dances that were chosen around the Philippines. The researcher used the notated dances to create a 3d image of the stage which varies whether these dances are performed in an open space or enclosed space. The lightings and acoustics were also considered in creating the performing arts complex. The said guidelines were then applied in the proposed project Sayawang Pambayan Performing Arts Complex.